Public Goods Policy Analysis: Case Study of Rice Import Policy by Perum Bulog in 2023 - Laksmi, Adinda Nafiza; Nurdin, Nurdin (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
Procurement of the public good of rice has economic and political impacts on the actors involved. The government, through Perum BULOG, 2023 will import rice from various countries. This government policy has created conflict between government institutions and farmer organizations. The government is of the view that rice imports in 2023 must be carried out to maintain food stability, rice which is the primary need of the Indonesian people. On the other hand, SPI and KRKP are of the view that the rice import policy is not based on the interests of domestic farmers. This research uses qualitative methods with data collection techniques carried out through literature study and interviews. The results of this research reinforce previous research that the practice of economic rent-seeking always occurs in government procurement of goods and services. Economic rent-seeking in the case of rice imports by Perum BULOG can occur due to the minimal role of this institution in controlling the price of rice produced by farmers. Apart from that, the conflict over the procurement of rice imports has been exploited by rice business people to gain economic profits during the harvest season and rice imports which will occur in the 2023 political year and ahead of the 2024 general election. can cover the costs of rice production. This research reveals how public policies can be used by certain parties for economic and political benefits.